ANALISIS PENGARUH BIAYA DISTRIBUSI, BIAYA PROMOSI DAN JUMLAH PEGAWAI PEMASARAN TERHADAP HASIL PENJUALAN - Lourensius L.T., Nerys (JURNAL ILMU MANAJEMEN, 2015)
This study aims to determine: (1) significant relationship between the cost of distribution, promotion and marketing headcount simultaneously against the sale at PT. Prima Athatama Magelang. (2) significant relationship between the cost of distribution, promotion and marketing headcount simultaneously against the sale at PT. Prima Athatama Magelang.          The research was conducted at PT. Prima Athatama Magelang. Data collection techniques used were interviews and observation techniques. The data obtained are qualitative and quantitative data. Peneitian objects are data on the number of distribution costs, promotional costs, the sheer number of employees of marketing and sales results have been achieved. In this study proposed two hypotheses: (1) Is there a significant relationship between the cost of distribution, promotion and marketing headcount partially against the sale at PT. Prima Athatama Magelang. (2) Is there a significant relationship between the cost of distribution, promotion and marketing headcount simultaneously against the sale at PT. Prima Athatama Magelang. Data analysis test of two hypotheses to be used multiple linear regression analysis with significance level of 5%, then before the data in the analysis test is conducted prior t test, F test, test R (determination) and classical assumption.The results showed that: (1) distribution costs, variable costs of promotion and marketing of variable number of employees partially have significant influence on sales results (Y) in PT. Prima Athatama Magelang evident because of the test results obtained by value t count t is greater than t Tabel is 3,475> 1,672. (2) distribution costs, variable costs of promotion and marketing of variable number of employees simultaneously have a significant impact on sales results (Y) in PT. Prima Athatama Magelang evident because of the test results obtained F count F count larger than F Tabel, namely 204, 811> 3,162. The results showed jointly have a significant impact on sales results (Y) in PT. Prima Athatama MagelangKata.